Equity private placements: The Malaysian experience 1999 - 2007 - Nordin, Norhafiza; Taufil Mohd, Kamarun Nisham (2010)
This study offers evidence concerning the announcement effect of equity private placements by examining the stock market reaction to the announcements made by Malaysian firms for the period 1999 to 2007.This study is motivated by empirical findings that unlike public placements, private placements are associated with positive announcement effect.Two prominent hypotheses used to explain the positive market responses are information and monitoring hypotheses.However, inconsistent with previous studies, we find zero announcement effect for Malaysian market.The result suggests that equity private placement in Malaysia does not convey positive signal as it does in other countries.